Front Cover: A Water Molecule Triggers Guest Exchange at a Mono‐Zinc Centre Confined in a Biomimetic Calixarene Pocket: a Model for Understanding Ligand Stability in Zn Proteins (Chem. Eur. J. 55/2021). Issue 55 (16th September 2021) - Brunetti, Emilio; Marcelis, Lionel; Zhurkin, Fedor E.; Luhmer, Michel; Jabin, Ivan; Reinaud, Olivia; Bartik, Kristin
Abstract : The ligand ‐exchange mechanism at a Zn II centre embedded in a calix[6]arene pocket was probed by NMR spectroscopy and DFT calculations. Results advocate for an associative exchange mechanism involving the transient exo‐coordination of a water molecule, giving rise to 5‐coordinate Zn II intermediates and inversion of the pyramid at the Zn II centre. These results are particularly relevant in the context of understanding the kinetic lability in Zn proteins and highlight the key role that a single water molecule can play in catalysing ligand exchange. More information can be found in the Full Paper by K. Bartik, O. Reinaud et al. (DOI: 10.1002/chem.20102184 ).